2017
DOI: 10.1002/ejsp.2238
|View full text |Cite
|
Sign up to set email alerts
|

The effect of red color on perceived self‐attractiveness

Abstract: Recent research showed that individuals are perceived as more attractive when presented with the color red. We seek to extend these findings by studying the effects of red color on individuals' perception of self‐attractiveness, rather than the attractiveness of others. Based on the color‐in‐context theory, we hypothesized that individuals would perceive themselves as more attractive under red chromatic conditions. In three experiments, participants were asked to wear a red or a blue shirt and rated their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…22 Previous studies state that women would also choose to wear red themselves or felt more attractive in red, more sexually receptive, and having a higher status. 6,24 Scaling analysis results from this study, which allow women to rank a selection of colors, show that women choose varying colors depending on the outfit they are wearing. Women generally preferred to wear the colors turquoise or blue with black bottoms or a single outfit, but not when wearing denim bottoms.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…22 Previous studies state that women would also choose to wear red themselves or felt more attractive in red, more sexually receptive, and having a higher status. 6,24 Scaling analysis results from this study, which allow women to rank a selection of colors, show that women choose varying colors depending on the outfit they are wearing. Women generally preferred to wear the colors turquoise or blue with black bottoms or a single outfit, but not when wearing denim bottoms.…”
Section: Discussionmentioning
confidence: 89%
“…[3][4][5] For humans, both genders use color to enhance their visual, aesthetic appearance in order to modify their self-image or to attract a significant other. 6,7 Make-up, hair dye, tattoos, accessories, or clothing are ways of using color in order to alter (permanently or temporary) or add "beauty" to one's aesthetic characteristics. 8 Color is used as a form of expression and a visual representation of an individual's social identity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…especially motivated to increase their attractiveness in order to obtain high-quality mates. In line with this idea, researchers have shown that wearers indeed perceive themselves to be more attractive when in red (Berthold, Reese, & Martin, 2017).…”
mentioning
confidence: 73%